2000
DOI: 10.4049/jimmunol.165.7.4127
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Production of C-C Chemokines by Individuals Infected with Human T Lymphotropic Virus Type II (HTLV-II) Alone and HTLV-II/HIV-1 Coinfected Individuals

Abstract: To investigate the immunological features of human T lymphotropic virus type II (HTLV-II) infection and specific mechanisms whereby HTLV-II might influence the progression of HIV-1 disease in coinfected individuals, we have analyzed the production of the C-C chemokines RANTES and macrophage inflammatory proteins 1α and 1β (MIP-1α and MIP-1β) by PBMCs from HTLV-II-infected and HTLV-II/HIV-1-coinfected individuals. We observed spontaneous production of significant levels of MIP-1α and -1β and, to a lesser extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…For example, various cytokines that were significantly altered in expression in LGL patients versus healthy controls are produced typically by CD8+ cells during viral infections, and some of them are almost invariably associated with viral processes. Examples of such cytokines include IFN-γ and chemokines CXCL10 (IP10) and CXCL8 (IL-8) [51][52][53][54][55]. Interestingly, up-regulation of phosphorylated AKT and ERK, previously found in LGL [36,56], can be caused by various chemokines such as CXCL8 (IL-8), which may prevent homeostatic apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, various cytokines that were significantly altered in expression in LGL patients versus healthy controls are produced typically by CD8+ cells during viral infections, and some of them are almost invariably associated with viral processes. Examples of such cytokines include IFN-γ and chemokines CXCL10 (IP10) and CXCL8 (IL-8) [51][52][53][54][55]. Interestingly, up-regulation of phosphorylated AKT and ERK, previously found in LGL [36,56], can be caused by various chemokines such as CXCL8 (IL-8), which may prevent homeostatic apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Human immunodeficiency virus infection of both activated and naive Th1 cells results in significant levels of RANTES, MIP-1␣, and MIP-1␤ by 4 to 6 days postinfection (3). In addition, PBMC obtained from individuals infected with human T-lymphotropic virus type II spontaneously secreted significant levels of MIP-1␣ and MIP-1␤ and to a lesser extent RANTES compared to uninfected controls (41). Both influenza A virus and Sendai virus infection of macrophages results in upregulation of, among others, RANTES, MIP-1␣, and MIP-1␤ (45).…”
Section: Vol 76 2002 Dengue Virus Induction Of Mast Cell Rantes 8415mentioning
confidence: 99%
“…In this regard, most seroprevalence studies have reported that HTLV-2 infection does not adversely affect the course of HIV-1 disease (8,19,20). Indeed, we and others have previously shown that HTLV-2 infection can potentially interfere with the replicative capacity of HIV-1 by up-regulating the secretion of HIV-1 suppressive chemokines, in particular C-C chemokine ligand 3/macrophage-inflammatory protein-1␣ (22,23).…”
Section: H Uman T Cell Leukemia Virus (Htlv)mentioning
confidence: 99%